HUBUNGAN POLA ASUH ORANG TUA TERHADAP KECERDASAN SPIRTUAL ANAK DI DESA TOAYA KECAMATAN SINDUE KABUPATEN DONGGALA - Nurfianti, Nurfianti; Alimuddin, Nurwahida; Jusmiati, Jusmiati (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2020)
This research was conducted with the background that the family is the main and appropriate place to cultivate the potential of children's spiritual intelligence. Children who are raised in a family environment with high spiritual intelligence will become individuals with high spiritual intelligence. The purpose of this study is to see how the parenting style is, to see how the child's spiritual intelligence is described, and to see how to do it. related to parenting patterns of parents with spiritual intelligence of children in Toaya Village, Sindue District, Donggala Regency. The research method used by researchers in this thesis is quantitative research with simple linear regression analysis. The study population was 240 children, for this study sample took a total of 60 samples, using a quota sampling technique. The data technique is in the form of a Likert scale questionnaire and uses interviews. Thus, based on the data processing that can be shown, there is no between parenting or parenting towards the spiritual intelligence of children in Toaya Village, Sindue District, Donggala Regency.